Distinct mechanisms eliminate mother and daughter centrioles in meiosis of starfish oocytes - Borrego-Pinto, Joana (2016)
Centriole elimination is an essential process that occurs in female meiosis of metazoa to reset centriole number in the zygote at fertilization. How centrioles are eliminated remains poorly understood. Here we visualize the entire elimination process live in starfish oocytes. Using specific fluorescent markers, we demonstrate that the two older, mother centrioles are selectively removed from the oocyte by extrusion into polar bodies. We show that this requires specific positioning of the second meiotic spindle, achieved by dynein-driven transport, and anchorage of the mother centriole to the plasma membrane via mother-specific appendages. In contrast, the single daughter centriole remaining in the egg is eliminated before the first embryonic cleavage. We demonstrate that these distinct elimination mechanisms are necessary because if mother centrioles are artificially retained, they cannot be inactivated, resulting in multipolar zygotic spindles. Thus, our findings reveal a dual mechanism to eliminate centrioles: mothers are physically removed, whereas daughters are eliminated in the cytoplasm, preparing the egg for fertilization.